Employee engagement for dummies - Kelleher, Bob. (Hoboken, NJ : John Wiley & Sons, 2014)
Learn to implement the necessary plans to create and sustain an engaging culture for your employees. This guide shows you how to attract and retain the best people while boosting their productivity, morale, and creativity.
Introduction -- Getting started with employee engagement -- Strategies for driving engagement -- Selecting the right employees to increase engagement -- Measuring and recognizing engagement -- The part of tens.
includes index.
Tặng
Keywords: Employee morale; Employee motivation